Development Of Powerpoint Learning Media For Mixed Drinks In The Food And Beverage Management Course - Maharani, Silvia; Masdarini, Luh; Sukerti, Ni Wayan (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to describe the development procedure of PowerPoint-based learning media on the topic of Mixed Beverages by applying the 4D development model (Define, Design, Develop, and Disseminate) in the Food an Beverage Management course and to determine its level of feasibility. The research method used is Research and Development (R&D)  with the 4D model. The data collection instrument consisted of validation questionnaires distributed to material experts, media experts, and instructional design experts. The validation results showed that the developed PowerPoint learning media obtained very feasible ratings from all three experts, namely 97% from the material expert, 94.2% from the media expert, and 95.6% from the instructional design expert. The assessments covered aspects of content feasibility, visual appearance, interactivity, and ease of use. Beyond its technical feasiility, this learning media also contributes to enhancing students’ procedural understanding and practical skills in creatively preparing mixed beverages in accordance with industry standards. Therefore, the PowerPoint learning media is declared highly feasible and effective as an innovative instructional tool to support the learning process in the Food and Beverage Management course within the Vocational Culinary Arts Education Study Program.